Job Safety Analysis and Hazard Identification of Welding Process in Semarang - JSA Method AS/NZS 4360:2004 - Ratih Pramitasari; Haikal Haikal; MG Catur Yuantari; Kristin Ishak Kurnia Dwi; Chalobon Treesak (Disease Prevention and Public Health Journal, 2021)
Background: The welding workshop in Semarang City is spread over several areas in Semarang City. There are several types of work in welding workshops, namely, cutting raw materials, assembling, welding, grinding, sanding, and painting. This study aimed to analyze occupational safety and health risks in the informal welding workshop using the JSA (Job Safety Analysis) AS/NZS 4360:2004 Risk Management method. Method: This research was conducted using semi-quantitative method with descriptive analysis. A cross-sectional research design was used because data (observations, interviews, filling in risk analysis tables, work accidents, occupational diseases, and controls) were collected at a particular time. The study was conducted in Semarang, Central Java, and the population was all informal welding workshops. Result: This study showed that there are 8 types of welding tasks, 21 potential hazards, and 24 health consequences in a welding process. The total score calculated by multiplying "chance" by "severity" shows that 11 health consequences were acceptable risk while 13 others were high risk. Conclusion: The highest score of occupational health hazards was electric shock due to chipped cable, electric shock due to a chipped short circuit, and wet/rain/cloudy work area. Welders are recommended to follow the proper instruction in the welding process, and each workshop must provide a first aid box for its workers.